2012
DOI: 10.4236/jsemat.2012.21002
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Processing Paramters on Metal Matrix Composites: Stir Casting Process

Abstract: Conventional stir casting process has been employed for producing discontinuous particle reinforced metal matrix composites for decades. The major problem of this process is to obtain sufficient wetting of particle by liquid metal and to get a homogenous dispersion of the ceramic particles. In the present study, aluminium metal matrix composites were fabricated by different processing temperatures with different holding time to understand the influence of process parameters on the distribution of particle in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
43
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(56 citation statements)
references
References 10 publications
1
43
0
Order By: Relevance
“…The effect of processing parameters such as processing temperature, holding time at constant stirring speed of 450 rpm on mechanical properties of Al/SiCp by stir casting process was studied by [13]. The results showed an improvement in microstructure at 700 o C and 850 o C processing temperatures and the hardness values also increases linearly with increasing processing temperatures from 750 °C to 800 °C at 20 minutes holding time.…”
Section: Introductionmentioning
confidence: 86%
“…The effect of processing parameters such as processing temperature, holding time at constant stirring speed of 450 rpm on mechanical properties of Al/SiCp by stir casting process was studied by [13]. The results showed an improvement in microstructure at 700 o C and 850 o C processing temperatures and the hardness values also increases linearly with increasing processing temperatures from 750 °C to 800 °C at 20 minutes holding time.…”
Section: Introductionmentioning
confidence: 86%
“…However, methods of achieving the following in stir casting are mostly to be considered: (i) no adverse chemical reaction between the reinforcement material and matrix alloy, (ii) no or very low porosity in the cast AMMCs, (iii) wettability between the two main phases, and (iv) achieving a uniform distribution of the reinforcement material. [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18] Some of the methods used to achieve these goals during stir casting of aluminum matrix composites are the modification of the alloy composition, coating or specific treatments to the reinforcements, and control of the process parameters (stirring temperature and time, etc.). [11][12][13][14] Among these, coating of the reinforcement is a successful technique used to prevent adverse interfacial reaction and promote wetting of the particles by aluminum through increasing the overall surface energy of the solid.…”
Section: Aluminum Metal Matrix Composites (Ammcs)mentioning
confidence: 99%
“…Due to these advantages, they are used in aerospace industries (airframe and aerospace components), automobile industries (engine pistons), and electronic components. [1][2][3][4][5][6][7][8] Many techniques have been developed for producing particulate-reinforced AMMCs, such as stir casting, squeeze casting, [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18] and powder metallurgy. [19][20][21] Although each of these methods has its own advantages and disadvantages, they are all relatively expensive.…”
Section: Aluminum Metal Matrix Composites (Ammcs)mentioning
confidence: 99%
“…Studies [2,4] have shown that porosity formation is attributed to gas entrapment during vigorous stirring leading to air bubbles in the slurry either independently or as air envelopes the reinforced particles. Very high stirring speed forms a vortex on the composite melt surface.…”
Section: Introductionmentioning
confidence: 99%
“…These features makes them to emerge as an important category of materials that have potentials for structural applications in the automotive and aerospace industry. The processing of this attractive material plays a major role in determining the performance properties under operational condition [2,3]. Among the variety of processing technique, the stir casting is generally accepted and commercially viable in developing the aluminium silicon carbide composite [4].…”
Section: Introductionmentioning
confidence: 99%